Selective Ablation of Pillar and Deiters' Cells Severely Affects Cochlear Postnatal Development and Hearing in Mice - Mellado Lagarde, Marcia M. (Society for Neuroscience, 2013)
Mammalian auditory hair cells (HCs) are inserted into a well structured environment of supporting cells (SCs) and acellular matrices. It has been proposed that when HCs are irreversibly damaged by noise or ototoxic drugs, surrounding SCs seal the epithelial surface and likely extend the survival of auditory neurons. Because SCs are more resistant to damage than HCs, the effects of primary SC loss on HC survival and hearing have received little attention. We used the Cre/loxP system in mice to specifically ablate pillar cells (PCs) and Deiters' cells (DCs). In Prox1CreER(T2)+/−;Rosa26(DTA/+) (Prox1DTA) mice, Cre-estrogen receptor (CreER) expression is driven by the endogenous Prox1 promoter and, in presence of tamoxifen, removes a stop codon in the Rosa26(DTA/+) allele and induces diphtheria toxin fragment A (DTA) expression. DTA produces cell-autonomous apoptosis. Prox1DTA mice injected with tamoxifen at postnatal days 0 (P0) and P1 show significant DC and outer PC loss at P2–P4, that reaches ∼70% by 1 month. Outer HC loss follows at P14 and is almost complete at 1 month, while inner HCs remain intact. Neural innervation to the outer HCs is disrupted in Prox1DTA mice and auditory brainstem response thresholds in adults are 40–50 dB higher than in controls. The hearing deficit correlates with loss of cochlear amplification. Remarkably, in Prox1DTA mice, the auditory epithelium preserves the ability to seal the reticular lamina and spiral ganglion neuron counts are normal, a key requirement for cochlear implant success. In addition, our results show that cochlear SC pools should be appropriately replenished during HC regeneration strategies.